SYSTEMIC DETERMINANTS OF GLOBAL FOOD SECURITY ENSURING GEOPOLITICAL TURBULENCE - KRAVCHUK, Nataliya; HOROCHOVSKY, Igor (Scientific journal «World of Finance», 2024)
Introduction. Recent events have demonstrated that the growth of geopolitical turbulence has a detrimental impact on the food security of the world’s poorest countries. Often, its consequences include economic wars, armed interstate conflicts, intrastate military-political confrontations, and economic crises. These factors ultimately lead to price increases and disruptions in food supply chains, resulting in increased poverty, limited access to fertile land, and, most importantly, the destruction of the foundations of the national economy. This, in turn, lowers the GDP per capita significantly, affecting the population’s consumer capabilities and jeopardizing a sufficient level of nutrition.The purpose of the is to generalize the systemic determinants of modern geopolitical turbulence and substantiate their impact on global food security while outlining recommendations aimed at enhancing the effectiveness of global institutions in ensuring the food security of the world’s poorest countries.Results. Systemic determinants of modern geopolitical turbulence are examined, and their impact on global food security is substantiated. The primary reasons for the increase in world food prices have been unveiled. A correlation analysis of indicators affecting the dynamics of the share and number of undernourished population, reflecting population income, the number of military conflicts, the level of global warming, and food prices, was carried out. Consequently, it has been proven that geopolitical turbulence has a significantly negative impact on food security in various countries worldwide. Notably, over the past 20-25 years, the African continent has become one of the main focal points of geopolitical conflicts, with their foundation rooted in the struggle for resources through political and military influence on the governments of certain African countries. The research has demonstrated that geopolitical conflicts and the risks associated with geopolitical turbulence are determinants exacerbating the food crisis in African countries.Conclusions. It has been proven that a country’s level of food security is closely related to the poverty level of its population. It is argued that humanitarian missions aimed at assisting malnourished populations will only postpone the resolution of hunger, while ongoing military and economic conflicts do not contribute to poverty reduction. It is substantiated that, in order to increase global food security, global organizations and geopolitical players should focus on the economic and political development of the world’s poorest countries, since the prolongation of both intrastate and interstate military-political conflicts serves as a source of geopolitical turbulence and exacerbates the global food crisis.